2020
DOI: 10.1017/s1751731120000907
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium deficiency suppresses follicle selection in laying ducks through mechanism involving cyclic adenosine monophosphate-mediated signaling pathway

Abstract: Ovarian follicle selection is a natural biological process in the pre-ovulatory hierarchy in birds that drives growing follicles to be selected within the ovulatory cycle. Follicle selection in birds is strictly regulated, involving signaling pathways mediated by dietary nutrients, gonadotrophic hormones and paracrine factors. This study aimed to test the hypothesis that dietary Ca may participate in regulating follicle selection in laying ducks through activating the signaling pathway of cyclic adenosine mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Calcium is involved in the meiotic cell cycles of mammalian oocytes [ 57 ]. In research conducted on birds, it has been found, that calcium may also play a role in increasing follicle growth [ 58 ]. It was found that Ca 2+ deficiency in the diet of laying birds reduced egg production (approximately 47% of Ca-adequate control diets containing 3.6% Ca).…”
Section: Electrolyte Balancementioning
confidence: 99%
See 3 more Smart Citations
“…Calcium is involved in the meiotic cell cycles of mammalian oocytes [ 57 ]. In research conducted on birds, it has been found, that calcium may also play a role in increasing follicle growth [ 58 ]. It was found that Ca 2+ deficiency in the diet of laying birds reduced egg production (approximately 47% of Ca-adequate control diets containing 3.6% Ca).…”
Section: Electrolyte Balancementioning
confidence: 99%
“…Moreover, the effect of calcium deficiency on the number of hierarchical follicles was limited (approximately 56% of Ca-adequate control diets containing 3.6% Ca). The authors also report that calcium deficiency in laying birds significantly limits the process of selecting pre-ovulatory follicles [ 58 ]. Moreover, the development of ovarian follicles in birds is orderly.…”
Section: Electrolyte Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Pre-clinical studies strongly reported the effect of calcium on follicular development. 25,26 Velazquez et al conducted a study on metformin and reported that insulin and androgen levels were reduced after 6 months of metformin therapy and regulating menstrual cycles in which fertility has been restored in patients with PCOS. 27 In the present study, more than 65% of study subjects not taking the recommended daily allowance of dietary products in all study groups i.e.…”
Section: Discussionmentioning
confidence: 99%